2022
DOI: 10.1002/jmv.27650
|View full text |Cite
|
Sign up to set email alerts
|

Construction and characterization of two SARS‐CoV‐2 minigenome replicon systems

Abstract: The ongoing COVID‐19 pandemic severely impacts global public health and economies. To facilitate research on severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) virology and antiviral discovery, a noninfectious viral replicon system operating under biosafety level 2 containment is warranted. We report herein the construction and characterization of two SARS‐CoV‐2 minigenome replicon systems. First, we constructed the IVT‐CoV2‐Rep complementary DNA template to generate a replicon messenger RNA (mRNA) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 67 publications
(173 reference statements)
2
23
0
Order By: Relevance
“…Notably, a recent study on SARS‐CoV‐2 replicon showed that BAC‐SARS‐CoV‐2 system can generate nonnatural spliced viral RNA species. 29 However, full‐length viral genomic RNA is known to be packaged preferentially. 30 Whether the spliced RNA species might be packaged into ΔS‐S‐Flag or ΔN‐N‐Flag leading to further attenuation of the BAC‐rescued single‐cycle virus requires further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a recent study on SARS‐CoV‐2 replicon showed that BAC‐SARS‐CoV‐2 system can generate nonnatural spliced viral RNA species. 29 However, full‐length viral genomic RNA is known to be packaged preferentially. 30 Whether the spliced RNA species might be packaged into ΔS‐S‐Flag or ΔN‐N‐Flag leading to further attenuation of the BAC‐rescued single‐cycle virus requires further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, we designed, constructed, and characterized a dual-promoter-driven and dual-reporter-expressing SARS2 replicon. Our replicon contained the genomic organization from 5′ end to 3′ end: LTR-T7-HHD Rz-5′UTR-NSP1-P2A-fLuc-IRES-NSP2-16-TRS-GFP::Bsr-TRS-N-ORF10-3′UTR-HDV Rz-BGH pA. Over the past two years, several SARS-CoV-2 replicons have been developed [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. The general genomic composition of these SARS-CoV-2 replicons includes 5′UTR, ORF1a/1b, a Luc gene or green fluorescence protein (GFP) reporter gene, N, and 3′UTR from 5′ end to 3′ end.…”
Section: Discussionmentioning
confidence: 99%
“…However, they differ in how the replicon RNA is produced. Some replicons have a T7 promoter at the 5′ end, and the replicon RNA has to be synthesized in vitro [ 59 , 60 , 61 , 62 , 63 , 64 ]. Other replicons have the human cytomegalovirus (CMV) immediate-early enhance and promoter at the 5′ end, and the replicon RNA is transcribed from the replicon DNA that is introduced into cells by transfection [ 65 , 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10] The SARS-CoV-2 genome consists of several functional genes, of which nucleocapsid (N) and spike (S) proteins are widely used in SARS-CoV-2 molecular and serological detection. [11][12][13] As the structural proteins, S and N, are expected to show high expression levels during infection. The S glycoprotein of SARS-CoV-2, which protrudes from the virus surface, plays an important role in viral infection through the specific molecular interaction of its receptorbinding domain (RBD) with the human angiotensin-converting enzyme 2 receptor (ACE2).…”
mentioning
confidence: 99%